1979
DOI: 10.1111/j.1439-0442.1979.tb01634.x
|View full text |Cite
|
Sign up to set email alerts
|

The Relative Importance of Dry‐ and Wet‐bulb Temperatures in the Thermorespiratory Function in the Chicken

Abstract: 15. STURKIE, P. D., 1970: Respiration in birds. I n : Duke's physiology of domestic animals, (SWENSON, M. J., ed.), 8th edition, Comstock Publishing Associates, N e w York.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

1983
1983
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…When protection is provided against heat, it is usually inadequate because it is in form of temporary light shade and radiation shield [9, 11, 12]. The report of Egbunike [13] suggests that the effect of a hot environment on the body of birds depends not only on the nature of the microclimatic factors involved, but also on their intensity. According to Egbunike [13], environment affects adversely the chicken.…”
Section: Effects Of Meteorological Elements On Domestic Chickensmentioning
confidence: 99%
See 2 more Smart Citations
“…When protection is provided against heat, it is usually inadequate because it is in form of temporary light shade and radiation shield [9, 11, 12]. The report of Egbunike [13] suggests that the effect of a hot environment on the body of birds depends not only on the nature of the microclimatic factors involved, but also on their intensity. According to Egbunike [13], environment affects adversely the chicken.…”
Section: Effects Of Meteorological Elements On Domestic Chickensmentioning
confidence: 99%
“…The report of Egbunike [13] suggests that the effect of a hot environment on the body of birds depends not only on the nature of the microclimatic factors involved, but also on their intensity. According to Egbunike [13], environment affects adversely the chicken. This observation corroborates the findings of Donald [14] that a greater number of physiological activities undergo specific changes in birds exposed to a hot environment.…”
Section: Effects Of Meteorological Elements On Domestic Chickensmentioning
confidence: 99%
See 1 more Smart Citation
“…(1). The Temperature Humidity Index, THI ( C), is the most frequently used name for these indices when they are applied to farm animals, and numerous authors [3][4][5][6][7][8][9] have suggested the use of THI to express the relative significance of air temperature and humidity on heat stress among confined pigs and poultry THI ¼ at db þ 1 À a ðÞ t wb (1) where a is the weighting of dry-bulb temperature; t db is the dry-bulb temperature ( C); t wb is the wet-bulb temperature ( C).…”
Section: Introductionmentioning
confidence: 99%
“…(1) is to expose animals to different combinations of air temperature and humidity and determine which a-value results in the best correlation between THI and measured response variables, which can be physiological parameters [3][4][5][6][7][8][9] or production parameters [10]. The resulting a-values differ from study to study, and if more response variables are included in the same study, the a-value may be different for the different response variables [4][5][6]8]. Most frequently, reported a-values lie in the interval between 0.6 and 0.9, and normally it appears that the a-values have to differ considerably from the value that resulted in the best correlation before it significantly degrades the correlation between the parameters used and THI.…”
Section: Introductionmentioning
confidence: 99%